Predicting College Completion Among Students With Learning Disabilities. (November 2018) - Yu, Meifang; Novak, Jeanne A.; Lavery, Matthew Ryan; Vostal, Brooks R.; Matuga, Julia M.
The authors analyzed National Longitudinal Transition Study–2 (NLTS2) data to examine the role of high school academic preparation and receipt of postsecondary academic support services (PASS) in predicting college completion among students with learning disabilities. Logistic regression analyses revealed that students who earned a 3.0 grade point average (GPA) in a college preparatory curriculum were more than twice as likely to complete college than those with a similar GPA who did not complete a college preparatory curriculum. Furthermore, among students who completed a college preparatory curriculum, earning a higher GPA and accessing PASS both dramatically increased the likelihood that they would complete college. Results underscore the importance of incorporating a college preparatory curriculum into transition planning for college-bound students with learning disabilities.